A method for preparing an oxidation-resistant heat-conductive PPS composite material and fiber, and PPS fiber
By using composite nanomaterials of graphene, nano zinc oxide and boron carbide in PPS fibers, the problem of easy oxidation in high-temperature environments is solved, its anti-oxidation and thermal conductivity are improved, its service life is extended and mechanical properties are retained.
Patent Information
- Application Number
- CN202510119877.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-25
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-25
AI Technical Summary
PPS fibers are easily oxidized and degraded in applications of high-temperature filter materials, resulting in loss of performance and shortened service life.
Graphene serves as a dispersion carrier to assist in the dispersion of nano zinc oxide and boron carbide, and replaces small molecule coupling agents or dispersants to better combine antioxidant components with PPS materials, improving their antioxidant and thermal conductivity.
It realizes the durability of the antioxidant properties of PPS fibers during long-term use, and maximizes its mechanical properties while improving thermal conductivity.
Smart Images

Figure CN119570252B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polyphenylene sulfide fibers, and more specifically, relates to a preparation method of an antioxidant heat-conductive PPS composite material and fiber, and a PPS fiber. Background Art
[0002] In order to improve the cleanliness of smoke emission, the industry uses bag dust collectors for smoke filtration. The dust capture rate of this dust bag is generally above 99%, which can effectively remove smoke pollutants in the exhaust gas. As the main material of the dust bag, its performance should not be affected by the strong corrosive components, harmful substances in the exhaust gas, and the comprehensive environment accompanied by high temperature, water vapor, etc. Therefore, the development of high temperature resistant filter materials that can achieve high efficiency and long-term filtration in high temperature flue gas has far-reaching significance for environmental protection.
[0003] Polyphenylene sulfide (PPS) fiber is a high-performance material with excellent high temperature resistance, chemical corrosion resistance, flame retardancy, good thermal stability, etc., so it is widely used in high-temperature filter materials. PPS staple fiber is used as the main raw material for high-temperature filter materials because of its low requirements for raw materials and processing and its relatively low price. With the continuous improvement of PPS fiber manufacturing level, PPS filaments are also constantly replacing staple fibers as the main raw material for high-temperature filter materials.
[0004] The disadvantage of PPS fiber as a high-temperature dust removal material is its poor oxidation resistance. In a high-temperature oxygen environment, the PPS molecular chain is easily oxidized, resulting in the breakage of its molecular chain and a significant decrease in fiber strength, which ultimately shortens the service life of the smoke filter bag. In order to alleviate the thermal oxidation rate of PPS fibers and increase the service life of PPS filter bags, PTFE fibers with good oxidation resistance are industrially compounded with PPS fibers to prepare PPS / PTFE composite filter bags. This method replaces PPS fibers with PTFE fibers with good oxidation resistance, thereby extending the service life of dust filter bags. However, this method does not fundamentally solve the problem of poor oxidation resistance of PPS.
[0005] The patent "A method for preparing anti-oxidation PPS fiber" (CN113818246A) treats the surface of PPS fiber with an anti-oxidation treatment liquid. The rough-surfaced PPS fiber is soaked in an anti-oxidation liquid mixed with deionized water, silane coupling agent, PTFE emulsion, adhesive, film-forming aid, and talcum powder, and then dried to obtain the anti-oxidation PPS fiber. Although this method is relatively convenient, the PPS fiber prepared by this method only contains anti-oxidation components on the surface, and the interior does not achieve the anti-oxidation effect. Moreover, the surface of the PPS fiber prepared at present is basically smooth and highly hydrophobic, which is very unfavorable for the adsorption, uniformity and firmness of the anti-oxidation liquid.
[0006] The patent "A polyphenylene sulfide antioxidant fiber based on layered nanoparticles and its preparation method" (CN108360085B) prepares graphene oxide by strong oxidizing acid, and then blends it with PPS after surface modification by benzimidazole salt surfactant to prepare antioxidant fiber. The graphene oxide prepared by this method has strong hydrophilicity. Although its surface hydrophilicity will be weakened after surfactant modification, it will still affect its dispersion in the highly hydrophobic PPS polymer matrix. At the same time, graphene oxide will form lamellar defects during the preparation process of strong oxidizing acid (concentrated sulfuric acid), thereby affecting the integrity of its lamellar structure, and thus weakening its oxygen barrier performance as a lamellar nanomaterial. This patent also uses small molecule surfactants (benzimidazole salt surface), the presence of which will reduce the strength and spinnability of PPS fibers.
[0007] The patent "Antioxidant polyphenylene sulfide / modified nano-silica composite fiber and preparation method thereof" (CN110205703B) modifies nano-silica particles with a silane coupling agent and blends them with PPS for melt spinning to obtain antioxidant PPS fibers. The small molecule coupling agent also used in this method will have a significant negative impact on the strength and spinnability of PPS fibers. Summary of the invention
[0008] The purpose of the present invention is to address the above shortcomings and provide a method for preparing an antioxidant thermally conductive PPS composite material and fiber and a PPS fiber prepared by the method, so as to solve the problem that PPS fiber is easily oxidized and degraded in high-temperature filter material applications, thereby leading to loss of performance and shortened service life; by adding and modifying the PPS material to improve its own antioxidant properties, using graphene as a dispersion carrier to assist the dispersion of nano zinc oxide and boron carbide, replacing the small molecule coupling agent or dispersant in the prior art, so that the antioxidant component and the PPS material are better combined together, which can ensure the durability of the antioxidant properties of the PPS fiber during long-term use and can maximize the retention of the mechanical properties of the PPS fiber itself.
[0009] To achieve the above object, the present invention is implemented by the following technical solutions:
[0010] In a first aspect, the present invention provides a method for preparing an oxidation-resistant thermally conductive PPS composite material, comprising:
[0011] The graphite / zinc nitrate / water mixture is placed in a hydrothermal synthesis reactor, reacted at 150°C to 210°C, cooled to room temperature after the reaction, and the supernatant is removed, and the reaction mixture is washed and dried to obtain zinc oxide pre-intercalated graphite powder;
[0012] The zinc oxide pre-intercalated graphite powder is ground and mixed with boron carbide nanoparticles and deionized water, and the ground mixture is dried to obtain a graphene / zinc oxide / boron carbide composite nanomaterial; wherein the mass ratio of the zinc oxide pre-intercalated graphite powder, boron carbide nanoparticles and deionized water is (5-20): (1-10): 1×10 4 ;
[0013] 0.1-5 parts by weight of the graphene / zinc oxide / boron carbide composite nanomaterial is mixed with 90-100 parts by weight of PPS powder to prepare a PPS nanocomposite material.
[0014] Furthermore, the preparation method of the graphite / zinc nitrate / water mixture comprises:
[0015] Deionized water and small-diameter flake graphite are ground and mixed at a grinding speed of 20-100 rpm for 10-60 min, and then zinc nitrate is added and the grinding and mixing is continued for 20-60 min. The pH value of the solution is adjusted to 9-11. The mass ratio of deionized water, small-diameter flake graphite and zinc nitrate is 1×10 4 : (0.5~5): (0.1~1).
[0016] Furthermore, the particle size of the small-diameter flake graphite is 8000 mesh to 12000 mesh.
[0017] Furthermore, the method for adjusting the pH value of the solution is:
[0018] The graphite / zinc nitrate / water mixture after grinding and mixing is heated and stirred, and a 0.1-2.0 mol / L sodium hydroxide aqueous solution is added dropwise to a pH value of 9-11.
[0019] Furthermore, the reaction time of preparing the zinc oxide pre-intercalated graphite / water mixture from the graphite / zinc nitrate / water mixture is 3 to 10 hours; the reaction mixture after removing the supernatant is washed with deionized water and ethanol for 2 to 3 times respectively; and spray drying is performed after washing.
[0020] Furthermore, the grinding and mixing time of the zinc oxide pre-intercalated graphite powder, boron carbide nanoparticles and deionized water is 1-4 hours, the grinding speed is 50-100 rpm, and the drying temperature is 90° C.-120° C.
[0021] Furthermore, the mixing speed of the graphene / zinc oxide / boron carbide composite nanomaterial and the PPS powder is 500-1500 rpm, the mixing time is 1-5 min, and the mixing temperature is 25-60 °C.
[0022] In a second aspect, the present invention further provides a method for preparing an oxidation-resistant thermally conductive PPS fiber, comprising:
[0023] Extruding and granulating the antioxidant and thermally conductive PPS composite material prepared by the method described in the first aspect to obtain composite PPS granules;
[0024] The composite PPS pellets are subjected to extrusion melting and spinning, and the obtained primary fibers are subjected to heat drawing and winding to obtain antioxidant thermal conductive PPS fibers.
[0025] Furthermore, the extrusion granulation adopts a twin-screw extruder, the extrusion temperature is 260° C. to 330° C., and the screw speed is 200 to 400 rpm.
[0026] Furthermore, the temperature of the extruder for extruding the melt is 270°C to 320°C; the temperature of the spinneret for spinning is 300°C to 330°C.
[0027] Furthermore, the temperature of the hot stretching is 90°C to 150°C, the stretching multiple is 2 to 5 times, and the stretching speed is 1000 to 2000 m / min.
[0028] In a third aspect, the present invention provides an oxidation-resistant thermally conductive PPS fiber, which is made by the preparation method described in the second aspect.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The present invention uses graphene as a dispersion carrier to assist in the dispersion of nano zinc oxide and boron carbide. The strong interface interaction between graphene and PPS can promote the dispersion of zinc oxide and boron carbide in PPS, reduce the agglomeration of zinc oxide and boron carbide between PPS, so as to achieve a uniform dispersion effect; the combination of uniformly dispersed zinc oxide and structurally complete graphene can effectively construct a heat conduction network in PPS, promote the dissipation of heat in the PPS matrix, and improve the thermal conductivity of PPS fiber; the combination of two-dimensional flaky graphene with good oxygen isolation effect and boron carbide with extremely high oxidation resistance and chemical resistance can significantly improve the oxidation resistance of PPS fiber;
[0031] The method of the present invention does not require the use of strong corrosive agents such as strong acids or strong bases, and is environmentally friendly and safe for mass production; does not require the use of small molecule dispersants or coupling agents, and can maximize the retention of the mechanical properties of the PPS fiber itself;
[0032] The invention prepares a small-diameter graphene / zinc oxide / boron carbide nanocomposite material by an intercalation-sand milling method. The graphene prepared by the method can retain its own complete microstructure, thereby effectively blocking the oxidation of PPS by oxygen; synthesizes nano zinc oxide particles between small-diameter flake graphite layers by a hydrothermal method, and then grinds and peels off the graphite pre-intercalated with zinc oxide by using boron carbide nanoparticles as a grinding aid, thereby preparing the graphene / zinc oxide / boron carbide nanocomposite material; zero-dimensional zinc oxide and boron carbide are dispersed and blocked from each other with two-dimensional graphene, thereby preventing the mutual aggregation of the same materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Schematic diagram of the preparation process of the graphene / zinc oxide / boron carbide composite nanomaterial according to an embodiment of the present invention. DETAILED DESCRIPTION
[0034] The preferred embodiments of the present invention will be described in more detail below in conjunction with the accompanying drawings and specific examples.
[0035] PPS powder: Chongqing Jushi New Materials Co., Ltd., millimeter-sized particles, brand: GAC 02;
[0036] Small flake graphite: Qingdao Hengrunda Graphite Products Co., Ltd., 12000 mesh flake graphite;
[0037] Zinc nitrate: Sigma-Aldrich, purity: 99.9%;
[0038] Sodium hydroxide: Sigma-Aldrich, purity: >98%;
[0039] Boron carbide: Anhui AVIC Nanotechnology Development Co., Ltd., average particle size: 50 nm, purity: 99.9%.
[0040] Example 1
[0041] This embodiment provides a method for preparing an oxidation-resistant thermally conductive PPS composite material and fiber, which specifically comprises the following steps:
[0042] Add 5×10 4 g deionized water, take 5 g of small-diameter flake graphite (8000 mesh~12000 mesh) and put it in a sand mill, turn on the sand mill for mixed grinding, the speed is 80 rpm, and the mixing time is 30 min; then, add 0.5 g of zinc nitrate into the sand mill and mix for 30 min; take the obtained graphite / zinc nitrate / water mixture out of the sand mill, slowly add 0.1 mol / L sodium hydroxide aqueous solution under mechanical stirring, and adjust the pH value of the solution to 10.
[0043] The mixed solution prepared above was added to a hydrothermal synthesis reactor and placed in an oven for reaction at a temperature of 180 °C for 6 h. After the reaction was completed, the reactor was taken out of the oven and cooled to room temperature. After removing the upper clear layer in the reactor, the reaction mixture was washed twice with deionized water and ethanol, respectively, and zinc oxide pre-intercalated graphite powder was obtained after spray drying.
[0044] Take 25 g of the zinc oxide pre-intercalated graphite powder, 5 g of boron carbide nanoparticles, 5×10 4 g of deionized water was added to a sand mill for grinding and mixing at a speed of 70 rpm for 2 h. After grinding, the mixture was dried in a spray dryer to remove moisture at a drying temperature of 105 °C, and finally a graphene / zinc oxide / boron carbide composite nanomaterial was obtained. The above preparation process is as follows Figure 1 shown.
[0045] Take 50 g of the graphene / zinc oxide / boron carbide nanocomposite prepared above and mix it with 10 KG PPS powder in a high-speed mixer for 3 min at a speed of 1000 rpm; after mixing, a graphene / zinc oxide / boron carbide / PPS composite material, i.e., an antioxidant and thermally conductive PPS composite material, is obtained.
[0046] The antioxidant and thermally conductive PPS composite material was added into a twin-screw machine for blending and granulation, wherein the extrusion temperature in each temperature zone was 260 / 270 / 280 / 290 / 300 / 310 / 320 / 320 / 320 / 310°C and the screw speed was 300 rpm; composite PPS pellets were obtained.
[0047] The composite PPS pellets obtained above are added to a single screw extruder, and the temperature of each temperature zone of the extruder is 270 / 290 / 300 / 310 / 315 / 320 ℃. After melt extrusion, it reaches the metering pump and then enters the spinneret. The spinneret temperature is 320 ℃. The nascent fibers passing through the spinneret are heat-drawn and wound to obtain PPS antioxidant long fibers. The temperature of the first hot roller is 100~120 ℃, the temperature of the second hot roller is 130~160 ℃, the temperature of the third hot roller is 170~200 ℃, the drafting multiple is 4 times, and the spinning speed is 1500 m / min, and the antioxidant thermal conductive PPS fiber is obtained.
[0048] Example 2
[0049] This embodiment provides a method for preparing an oxidation-resistant thermally conductive PPS composite material and fiber, which specifically comprises the following steps:
[0050] Add 5×10 4g deionized water, take 5 g of small-diameter flake graphite (8000 mesh ~ 12000 mesh) and put it in a sand mill, turn on the sand mill for mixed grinding, the speed is 80 rpm, and the mixing time is 30 min. Then, add 1 g of zinc nitrate to the sand mill and mix for 30 min. Take out the graphite / zinc nitrate / water mixture from the sand mill, slowly add 0.1 mol / L sodium hydroxide aqueous solution under mechanical stirring, and adjust the solution pH to 10.
[0051] After the mixed solution prepared above was added to the hydrothermal synthesis reactor, it was placed in an oven for reaction at a reaction temperature of 180 °C and a reaction time of 6 h. After the reaction was completed, the reactor was taken out of the oven and cooled to room temperature; after removing the upper clear night in the reactor, the reaction mixture was washed twice with deionized water and ethanol respectively, and zinc oxide pre-intercalated graphite powder was obtained after spray drying.
[0052] Take 25 g of the zinc oxide pre-intercalated graphite powder, 5 g of boron carbide nanoparticles, 5×10 4 g deionized water was added into a sand mill for grinding and mixing at a rotation speed of 70 rpm and a grinding time of 2 h. After grinding, the mixed solution was dried in a spray dryer to remove moisture at a drying temperature of 105 °C, and finally a graphene / zinc oxide / boron carbide composite nanomaterial was obtained.
[0053] Take 50 g of the graphene / zinc oxide / boron carbide nanocomposite prepared above and mix it with 10 KG PPS powder in a high-speed mixer for 3 min at a speed of 1000 rpm; after mixing, a graphene / zinc oxide / boron carbide / PPS composite material, i.e., an antioxidant and thermally conductive PPS composite material, is obtained.
[0054] The antioxidant and thermally conductive PPS composite material was added into a twin-screw machine for blending and granulation, wherein the extrusion temperature in each temperature zone was 260 / 270 / 280 / 290 / 300 / 310 / 320 / 320 / 320 / 310°C and the screw speed was 300 rpm; composite PPS pellets were obtained.
[0055] The composite PPS pellets obtained above are added to a single screw extruder, and the temperature of each temperature zone of the extruder is 270 / 290 / 300 / 310 / 315 / 320 ℃. After melt extrusion, it reaches the metering pump and then enters the spinneret. The spinneret temperature is 320℃. The nascent fibers passing through the spinneret are thermally stretched and wound to obtain PPS antioxidant long fibers. The temperature of the first hot roller is 100~120 ℃, the temperature of the second hot roller is 130~160 ℃, the temperature of the third hot roller is 170~200 ℃, the stretching multiple is 4 times, and the spinning speed is 1500 m / min, and the antioxidant thermal conductive PPS fiber is obtained.
[0056] Example 3
[0057] This embodiment provides a method for preparing an oxidation-resistant thermally conductive PPS composite material and fiber, which specifically comprises the following steps:
[0058] Add 5×10 4 g deionized water, take 5 g of small-diameter flake graphite (8000 mesh ~ 12000 mesh) and put it in a sand mill, turn on the sand mill for mixed grinding, the speed is 80 rpm, and the mixing time is 30 min. Then, add 2 g of zinc nitrate to the sand mill and mix for 30 min; take out the graphite / zinc nitrate / water mixture from the sand mill, slowly add 0.1 mol / L sodium hydroxide aqueous solution under mechanical stirring, and adjust the solution pH to 10.
[0059] After the mixed solution prepared above was added to the hydrothermal synthesis reactor, it was placed in an oven for reaction at a reaction temperature of 180 °C and a reaction time of 6 h. After the reaction was completed, the reactor was taken out of the oven and cooled to room temperature; after removing the upper clear night in the reactor, the reaction mixture was washed twice with deionized water and ethanol respectively, and zinc oxide pre-intercalated graphite powder was obtained after spray drying.
[0060] Take 25g of the above zinc oxide pre-intercalated graphite powder, 5g of boron carbide nanoparticles, 5×10 4 g deionized water was added into a sand mill for grinding and mixing at a rotation speed of 70 rpm and a grinding time of 2 h. After grinding, the mixed solution was dried in a spray dryer to remove moisture at a drying temperature of 105 °C, and finally a graphene / zinc oxide / boron carbide composite nanomaterial was obtained.
[0061] Take 50 g of the graphene / zinc oxide / boron carbide nanocomposite prepared above and mix it with 10 KG PPS powder in a high-speed mixer for 3 min at a speed of 1000 rpm; after mixing, a graphene / zinc oxide / boron carbide / PPS composite material, i.e., an antioxidant and thermally conductive PPS composite material, is obtained.
[0062] The above-mentioned antioxidant and thermally conductive PPS composite material was added to a twin-screw machine for blending and granulation. The extrusion temperatures in each temperature zone were 260 / 270 / 280 / 290 / 300 / 310 / 320 / 320 / 320 / 310°C and the screw speed was 300 rpm to obtain composite PPS pellets.
[0063] The composite PPS pellets obtained above are added to a single screw extruder, and the extruder temperature is 270 / 290 / 300 / 310 / 315 / 320 ℃. After melt extrusion, it reaches the metering pump and then enters the spinneret. The spinneret temperature is 320 ℃. The nascent fibers passing through the spinneret are heat-drawn and wound to obtain PPS antioxidant long fibers. The temperature of the first hot roller is 100~120℃, the temperature of the second hot roller is 130~160℃, the temperature of the third hot roller is 170~200℃, the drafting multiple is 4 times, and the spinning speed is 1500m / min to obtain antioxidant thermal conductive PPS fibers.
[0064] Example 4
[0065] This embodiment provides a method for preparing an oxidation-resistant thermally conductive PPS composite material and fiber, which specifically comprises the following steps:
[0066] Add 5×10 4 g deionized water, take 5 g of small-diameter flake graphite (8000 mesh~12000 mesh) and put it in a sand mill, turn on the sand mill for mixed grinding, the speed is 80 rpm, and the mixing time is 30 min; then, add 2 g of zinc nitrate into the sand mill and mix for 30 min; take out the graphite / zinc nitrate / water mixture from the sand mill, slowly add 0.1 mol / L sodium hydroxide aqueous solution under mechanical stirring, and adjust the pH value of the solution to 10.
[0067] The mixed solution prepared above was added to a hydrothermal synthesis reactor and placed in an oven for reaction at a temperature of 180 °C for 6 h. After the reaction was completed, the reactor was taken out of the oven and cooled to room temperature. After removing the upper clear layer in the reactor, the reaction mixture was washed twice with deionized water and ethanol, respectively, and zinc oxide pre-intercalated graphite powder was obtained after spray drying.
[0068] Take 25 g of the zinc oxide pre-intercalated graphite powder, 10 g of boron carbide nanoparticles, 5×10 4 g of deionized water was added to a sand mill for grinding and mixing at a speed of 70 rpm for 2 h. After grinding, the mixed solution was dried in a spray dryer to remove moisture at a drying temperature of 105 °C, and finally a graphene / zinc oxide / boron carbide composite nanomaterial was obtained.
[0069] Take 50 g of the graphene / zinc oxide / boron carbide nanocomposite prepared above and mix it with 10 KG PPS powder in a high-speed mixer for 3 min at a speed of 1000 rpm; after mixing, a graphene / zinc oxide / boron carbide / PPS composite material, i.e., an antioxidant and thermally conductive PPS composite material, is obtained.
[0070] The above-mentioned antioxidant and thermally conductive PPS composite material was added to a twin-screw machine for blending and granulation, wherein the extrusion temperature in each temperature zone was 260 / 270 / 280 / 290 / 300 / 310 / 320 / 320 / 320 / 310°C and the screw speed was 300 rpm to obtain composite PPS pellets.
[0071] The composite PPS pellets obtained above are added to a single screw extruder, and the extruder temperature is 270 / 290 / 300 / 310 / 315 / 320 ℃. After melt extrusion, it reaches the metering pump and then enters the spinneret. The spinneret temperature is 320℃. The nascent fibers passing through the spinneret are heat-drawn and wound to obtain PPS antioxidant long fibers. The temperature of the first hot roller is 100~120℃, the temperature of the second hot roller is 130~160℃, the temperature of the third hot roller is 170~200℃, the drafting multiple is 4 times, and the spinning speed is 1500m / min to obtain antioxidant thermal conductive PPS fibers.
[0072] Example 5
[0073] This embodiment provides a method for preparing an oxidation-resistant thermally conductive PPS composite material and fiber, which specifically comprises the following steps:
[0074] Add 5×10 4 g deionized water, take 5 g of small-diameter flake graphite (8000 mesh~12000 mesh) and put it in a sand mill, turn on the sand mill for mixed grinding, the speed is 80 rpm, and the mixing time is 30 min. Then, add 2 g of zinc nitrate to the sand mill and mix for 30 min; take out the graphite / zinc nitrate / water mixture from the sand mill, slowly add 0.1 mol / L sodium hydroxide aqueous solution under mechanical stirring, and adjust the solution pH to 10.
[0075] After adding the prepared mixed solution into the hydrothermal synthesis reactor, the mixture was placed in an oven for reaction at a temperature of 180 °C for 6 h. After the reaction was completed, the reactor was taken out of the oven and cooled to room temperature. After removing the upper clear water in the reactor, the reaction mixture was washed twice with deionized water and ethanol respectively, and zinc oxide pre-intercalated graphite powder was obtained after spray drying.
[0076] Take 25 g of the zinc oxide pre-intercalated graphite powder, 15 g of boron carbide nanoparticles, 5×10 4 g deionized water was added into a sand mill for grinding and mixing at a rotation speed of 70 rpm and a grinding time of 2 h. After grinding, the mixed solution was dried in a spray dryer to remove moisture at a drying temperature of 105 °C, and finally a graphene / zinc oxide / boron carbide composite nanomaterial was obtained.
[0077] Take 50 g of the graphene / zinc oxide / boron carbide nanocomposite prepared above and mix it with 10 KG PPS powder in a high-speed mixer for 3 min at a speed of 1000 rpm; after mixing, a graphene / zinc oxide / boron carbide / PPS composite material, i.e., an antioxidant and thermally conductive PPS composite material, is obtained.
[0078] The antioxidant and thermally conductive PPS composite material is added to a twin-screw machine for blending and granulation, wherein the extrusion temperature in each temperature zone is 260 / 270 / 280 / 290 / 300 / 310 / 320 / 320 / 320 / 310°C and the screw speed is 300 rpm; composite PPS pellets are obtained.
[0079] The composite PPS pellets obtained above are added to a single screw extruder, and the extruder temperature is 270 / 290 / 300 / 310 / 315 / 320 ℃. After melt extrusion, it reaches the metering pump and then enters the spinneret. The spinneret temperature is 320 ℃. The nascent fibers passing through the spinneret are heat-drawn and wound to obtain PPS antioxidant long fibers. The temperature of the first hot roller is 100~120℃, the temperature of the second hot roller is 130~160℃, the temperature of the third hot roller is 170~200℃, the drafting multiple is 4 times, and the spinning speed is 1500m / min to obtain antioxidant thermal conductive PPS fibers.
[0080] Example 6
[0081] This embodiment provides a method for preparing an oxidation-resistant thermally conductive PPS composite material and fiber, which specifically comprises the following steps:
[0082] Add 5×10 4 g deionized water, take 5 g of small-diameter flake graphite (8000 mesh~12000 mesh) and put it in a sand mill, turn on the sand mill for mixed grinding, the speed is 80 rpm, and the mixing time is 30 min; then, add 1 g of zinc nitrate into the sand mill and mix for 30 min; take out the graphite / zinc nitrate / water mixture from the sand mill, slowly add 0.1 mol / L sodium hydroxide aqueous solution under mechanical stirring, and adjust the pH value of the solution to 10.
[0083] The mixed solution prepared above was added to a hydrothermal synthesis reactor and placed in an oven for reaction at a temperature of 180 °C for 6 h. After the reaction was completed, the reactor was taken out of the oven and cooled to room temperature. After removing the upper clear layer in the reactor, the reaction mixture was washed twice with deionized water and ethanol, respectively, and zinc oxide pre-intercalated graphite powder was obtained after spray drying.
[0084] Take 25 g of the zinc oxide pre-intercalated graphite powder, 5 g of boron carbide nanoparticles, 5×10 4g deionized water was added into a sand mill for grinding and mixing at a rotation speed of 70 rpm and a grinding time of 2 h. After grinding, the mixed solution was dried in a spray dryer to remove moisture at a drying temperature of 105 °C, and finally a graphene / zinc oxide / boron carbide composite nanomaterial was obtained.
[0085] Take 10 g of the graphene / zinc oxide / boron carbide nanocomposite prepared above and mix it with 10 KG PPS powder in a high-speed mixer for 3 min at a speed of 1000 rpm; after mixing, a graphene / zinc oxide / boron carbide / PPS composite material, i.e., an antioxidant and thermally conductive PPS composite material, is obtained.
[0086] The antioxidant and thermally conductive PPS composite material was added into a twin-screw machine for blending and granulation, wherein the extrusion temperature in each temperature zone was 260 / 270 / 280 / 290 / 300 / 310 / 320 / 320 / 320 / 310°C and the screw speed was 300 rpm; composite PPS pellets were obtained.
[0087] The composite PPS pellets obtained above are added to a single screw extruder, and the extruder temperature is 270 / 290 / 300 / 310 / 315 / 320 ℃. After melt extrusion, it reaches the metering pump and then enters the spinneret. The spinneret temperature is 320℃. The nascent fibers passing through the spinneret are heat-drawn and wound to obtain PPS antioxidant long fibers. The temperature of the first hot roller is 100~120℃, the temperature of the second hot roller is 130~160℃, the temperature of the third hot roller is 170~200℃, the drafting multiple is 4 times, and the spinning speed is 1500m / min to obtain antioxidant thermal conductive PPS fibers.
[0088] Example 7
[0089] This embodiment provides a method for preparing an oxidation-resistant thermally conductive PPS composite material and fiber, which specifically comprises the following steps:
[0090] Add 5×10 4 g deionized water, take 5 g of small-diameter flake graphite (8000 mesh~12000 mesh) and put it in a sand mill, turn on the sand mill for mixed grinding, the speed is 80 rpm, and the mixing time is 30 min; then, add 1 g of zinc nitrate into the sand mill and mix for 30 min; take out the graphite / zinc nitrate / water mixture from the sand mill, slowly add 0.1 mol / L sodium hydroxide aqueous solution under mechanical stirring, and adjust the pH value of the solution to 10.
[0091] The mixed solution prepared above was added to a hydrothermal synthesis reactor and placed in an oven for reaction at a temperature of 180 °C for 6 h. After the reaction was completed, the reactor was taken out of the oven and cooled to room temperature. After removing the upper clear layer in the reactor, the reaction mixture was washed twice with deionized water and ethanol, respectively, and zinc oxide pre-intercalated graphite powder was obtained after spray drying.
[0092] Take 25 g of the zinc oxide pre-intercalated graphite powder, 5 g of boron carbide nanoparticles, 5×10 4 g deionized water was added into a sand mill for grinding and mixing at a rotation speed of 70 rpm and a grinding time of 2 h. After grinding, the mixed solution was dried in a spray dryer to remove moisture at a drying temperature of 105 °C, and finally a graphene / zinc oxide / boron carbide composite nanomaterial was obtained.
[0093] Take 500 g of the graphene / zinc oxide / boron carbide nanocomposite prepared above and mix it with 10 KG PPS powder in a high-speed mixer for 3 min at a speed of 1000 rpm; after mixing, a graphene / zinc oxide / boron carbide / PPS composite material, i.e., an antioxidant and thermally conductive PPS composite material, is obtained.
[0094] The antioxidant and thermally conductive PPS composite material is added to a twin-screw machine for blending and granulation, wherein the extrusion temperature in each temperature zone is 260 / 270 / 280 / 290 / 300 / 310 / 320 / 320 / 320 / 310°C and the screw speed is 300 rpm; composite PPS pellets are obtained.
[0095] The composite PPS pellets obtained above are added to a single screw extruder, and the extruder temperature is 270 / 290 / 300 / 310 / 315 / 320 ℃. After melt extrusion, it reaches the metering pump and then enters the spinneret. The spinneret temperature is 320 ℃. The nascent fibers passing through the spinneret are heat-drawn and wound to obtain PPS antioxidant long fibers. The temperature of the first hot roller is 100~120℃, the temperature of the second hot roller is 130~160℃, the temperature of the third hot roller is 170~200℃, the drafting multiple is 4 times, and the spinning speed is 1500m / min to obtain antioxidant thermal conductive PPS fibers.
[0096] Comparative Example 1
[0097] 10 KG PPS powder was added to the twin screw for extrusion granulation to obtain PPS spinning chips. The PPS spinning chips were added to the single screw of the spinning machine, and the extruder temperature was 270 / 290 / 300 / 310 / 315 / 320 ℃. After melting, the PPS melt reached the metering pump and then entered the spinneret. The spinneret temperature was 320 ℃. The nascent fibers passing through the spinneret were heat-stretched and wound to obtain PPS antioxidant long fibers. The temperature of the first hot roller was 100~120 ℃, the temperature of the second hot roller was 130~160 ℃, the temperature of the third hot roller was 170~200 ℃, the stretching multiple was 4 times, and the spinning speed was 1500 m / min to obtain PPS fibers.
[0098] Comparative Example 2
[0099] Take 1 g of zinc nitrate and dissolve it in 60 mL of water. Slowly add 0.1 mol / L sodium hydroxide aqueous solution under mechanical stirring to adjust the pH value of the solution to 10. After adding the mixed solution prepared above to the hydrothermal synthesis reactor, place it in an oven for reaction at a reaction temperature of 180 °C and a reaction time of 6 h. After the reaction is completed, take the reactor out of the oven and cool it to room temperature. After removing the upper clear night in the reactor, wash the reaction mixture twice with deionized water and ethanol respectively, and obtain zinc oxide powder after spray drying.
[0100] Take 25g zinc oxide powder, 5g boron carbide nanoparticles, 5×10 4 g of deionized water was added to a sand mill for grinding and mixing at a speed of 70 rpm for 2 h. After grinding, the mixed solution was dried in a spray dryer to remove moisture at a drying temperature of 105 °C, and finally a zinc oxide / boron carbide composite nanomaterial was obtained.
[0101] Take 50 g of the zinc oxide / boron carbide nanocomposite prepared above and 10 KG PPS powder and mix them in a high mixer for 3 min at a speed of 1000 rpm. After mixing, add the mixture to a twin-screw machine for blending and granulation to obtain a zinc oxide / boron carbide / PPS composite material. The extrusion temperature in each temperature zone is 260 / 270 / 280 / 290 / 300 / 310 / 320 / 320 / 320 / 310℃, and the screw speed is 300 rpm. Add the PPS nanocomposite material to a single screw extruder at an extruder temperature of 270 / 290 / 300 / 310 / 315 / 320℃. After melt extrusion, it reaches the metering pump and then enters the spinneret at a spinneret temperature of 320℃. The nascent fibers passing through the spinneret are thermally stretched and wound to obtain PPS antioxidant long fibers. The temperature of the first hot roller is 100-120°C, the temperature of the second hot roller is 130-160°C, the temperature of the third hot roller is 170-200°C, the drafting multiple is 4 times, the spinning speed is 1500 m / min, and PPS fiber is obtained.
[0102] Comparative Example 3
[0103] Add 5×10 4 g deionized water, take 5 g of small-diameter flake graphite and put it into a sand mill, turn on the sand mill for mixing and grinding, the speed is 80 rpm, and the mixing time is 30 min. After the mixing is completed, the water is removed by spray drying to obtain the ground graphite powder. Take 25 g of ground graphite powder, 5 g of boron carbide nanoparticles, 5×10 4 g of deionized water was added to a sand mill for grinding and mixing at a speed of 70 rpm for 2 h. After grinding, the mixed solution was dried in a spray dryer to remove moisture at a drying temperature of 105 °C, and finally a graphene / boron carbide composite nanomaterial was obtained.
[0104] Take 50 g of the graphene / boron carbide nanocomposite prepared above and 10 KG PPS powder and mix them in a high mixer for 3 min at a speed of 1000 rpm. After mixing, add the mixture to a twin-screw machine for blending and granulation to obtain a graphene / boron carbide / PPS composite material. The extrusion temperature in each temperature zone is 260 / 270 / 280 / 290 / 300 / 310 / 320 / 320 / 320 / 310°C, and the screw speed is 300 rpm. Add the PPS nanocomposite material to a single screw extruder at an extruder temperature of 270 / 290 / 300 / 310 / 315 / 320°C. After melt extrusion, it reaches the metering pump and then enters the spinneret at a spinneret temperature of 320°C. The nascent fibers passing through the spinneret are thermally stretched and wound to obtain PPS antioxidant long fibers. The temperature of the first hot roller is 100-120°C, the temperature of the second hot roller is 130-160°C, the temperature of the third hot roller is 170-200°C, the drafting multiple is 4 times, the spinning speed is 1500 m / min, and PPS fiber is obtained.
[0105] Comparative Example 4
[0106] This embodiment provides a method for preparing an oxidation-resistant thermally conductive PPS composite material and fiber, which specifically comprises the following steps:
[0107] Add 5×10 4 g deionized water, take 5 g of small-diameter flake graphite (8000 mesh~12000 mesh) and put it in a sand mill, turn on the sand mill for mixed grinding, the speed is 80 rpm, and the mixing time is 30 min; then, add 1 g of zinc nitrate into the sand mill and mix for 30 min; take out the graphite / zinc nitrate / water mixture from the sand mill, slowly add 0.1 mol / L sodium hydroxide aqueous solution under mechanical stirring, and adjust the pH value of the solution to 10.
[0108] The mixed solution prepared above was added to a hydrothermal synthesis reactor and placed in an oven for reaction at a temperature of 180 °C for 6 h. After the reaction was completed, the reactor was taken out of the oven and cooled to room temperature. After removing the upper clear layer in the reactor, the reaction mixture was washed twice with deionized water and ethanol, respectively, and zinc oxide pre-intercalated graphite powder was obtained after spray drying.
[0109] Take 25 g of the zinc oxide pre-intercalated graphite powder, 5×10 4 g deionized water was added into a sand mill for grinding and mixing at a rotation speed of 70 rpm and a grinding time of 2 h. After grinding, the mixed solution was dried in a spray dryer to remove moisture at a drying temperature of 105 °C, and finally a graphene / zinc oxide composite nanomaterial was obtained.
[0110] 50 g of the graphene / zinc oxide nanocomposite prepared above was taken and mixed with 10 KG PPS powder in a high-speed mixer for 3 min at a speed of 1000 rpm; after the mixing was completed, a graphene / zinc oxide / PPS composite material, i.e., an antioxidant and thermally conductive PPS composite material, was obtained.
[0111] The antioxidant and thermally conductive PPS composite material is added to a twin-screw machine for blending and granulation, wherein the extrusion temperature in each temperature zone is 260 / 270 / 280 / 290 / 300 / 310 / 320 / 320 / 320 / 310°C and the screw speed is 300 rpm; composite PPS pellets are obtained.
[0112] The composite PPS pellets obtained above are added into a single screw extruder with an extruder temperature of 270 / 290 / 300 / 310 / 315 / 320 °C. After melt extrusion, they reach the metering pump and then enter the spinneret with a spinneret temperature of 320 °C. The nascent fibers passing through the spinneret are subjected to hot drawing and winding to obtain PPS antioxidant long fibers with a drawing temperature of 90-120 °C, a drawing multiple of 4 times, and a spinning speed of 1500 m / min to obtain antioxidant thermal conductive PPS fibers.
[0113] The PPS long fibers prepared in the above-mentioned embodiments and comparative examples were subjected to oxidation treatment (2 mol / L sulfuric acid / nitric acid mixed solution, 80° C., 72 h), and the breaking strength before and after oxidation was tested. The comparison results are shown in Table 1.
[0114] Table 1: Performance test comparison of PPS long fibers obtained in various embodiments and comparative examples
[0115] .
[0116] According to the data in the table, Examples 1 to 3 show that as Zn(NO 3 ) 2 The intercalation degree of graphite increases with the increase of Zn(NO) content. During the sanding process, graphite with a high degree of pre-intercalation can be better exfoliated to form graphene. The amount of graphene will increase with the increase of Zn(NO 3 ) 2 As the content of the graphene increases, the number of graphene sheets will decrease, the oxygen barrier and synergistic dispersion effects will be more obvious, the construction of the thermal network will be more perfect, and the thermal conductivity efficiency will be higher. 4With the increase of C content, the efficiency of sand milling is greatly improved, the stripping efficiency of pre-intercalated graphite is significantly increased, the number of graphene prepared is increased, the number of layers is reduced, the oxygen barrier and synergistic dispersion effects are more obvious, and the thermal conductivity is also improved. Example 2, Example 6 and Example 7 are cases with different amounts of composite powder added. With the increase of the amount of composite powder, the oxidation resistance and thermal conductivity of PPS fiber are significantly improved.
[0117] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Without departing from the scope and technical principles of the described embodiments, many modifications and changes are obvious to those of ordinary skill in the art, and these modifications and changes should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an antioxidant thermally conductive PPS composite material, characterized in that: include: The graphite / zinc nitrate / water mixture is placed in a hydrothermal synthesis reactor, reacted at 150°C to 210°C, cooled to room temperature after the reaction, and the supernatant is removed, and the reaction mixture is washed and dried to obtain zinc oxide pre-intercalated graphite powder; The zinc oxide pre-intercalated graphite powder is ground and mixed with boron carbide nanoparticles and deionized water, and the ground mixture is dried to obtain a graphene / zinc oxide / boron carbide composite nanomaterial; wherein the mass ratio of the zinc oxide pre-intercalated graphite powder, boron carbide nanoparticles and deionized water is (5-20): (1-10): 1×10 4 ; 0.1-5 parts by weight of the graphene / zinc oxide / boron carbide composite nanomaterial is mixed with 90-100 parts by weight of PPS powder to prepare a PPS nanocomposite material.
2. The method for preparing the antioxidant thermally conductive PPS composite material according to claim 1, characterized in that: The preparation method of the graphite / zinc nitrate / water mixed solution comprises: Deionized water and small-diameter flake graphite are ground and mixed at a grinding speed of 20-100 rpm for 10-60 min, and then zinc nitrate is added and the grinding and mixing is continued for 20-60 min. The pH value of the solution is adjusted to 9-11. The mass ratio of deionized water, small-diameter flake graphite and zinc nitrate is 1×10 4 : (0.5~5): (0.1~1).
3. The method for preparing the antioxidant thermally conductive PPS composite material according to claim 2, characterized in that: The particle size of the small-diameter flake graphite is 8000 mesh to 12000 mesh.
4. The method for preparing the antioxidant thermally conductive PPS composite material according to claim 2, characterized in that: The method for adjusting the pH value of the solution is: The graphite / zinc nitrate / water mixture after grinding and mixing is heated and stirred, and a 0.1-2.0 mol / L sodium hydroxide aqueous solution is added dropwise to a pH value of 9-11.
5. The method for preparing the antioxidant thermally conductive PPS composite material according to claim 1, characterized in that: The reaction time of preparing the zinc oxide pre-intercalated graphite / water mixture from the graphite / zinc nitrate / water mixture is 3-10 hours; the reaction mixture after removing the supernatant is washed with deionized water and ethanol for 2-3 times respectively; and spray drying is adopted after washing.
6. The method for preparing the antioxidant thermally conductive PPS composite material according to claim 1, characterized in that: The grinding and mixing time of the zinc oxide pre-intercalated graphite powder, boron carbide nanoparticles and deionized water is 1-4 hours, the grinding speed is 50-100 rpm, and the drying temperature is 90° C.-120° C.
7. The method for preparing the antioxidant thermally conductive PPS composite material according to claim 1, characterized in that: The graphene / zinc oxide / boron carbide composite nanomaterial and PPS powder are mixed at a rotation speed of 500-1500 rpm, a mixing time of 1-5 min, and a mixing temperature of 25-60 °C.
8. A method for preparing an oxidation-resistant thermally conductive PPS fiber, characterized in that: include: Extruding and granulating the antioxidant thermally conductive PPS composite material prepared by the method according to any one of claims 1 to 7 to obtain composite PPS granules; The composite PPS pellets are subjected to extrusion melting and spinning, and the obtained primary fibers are subjected to heat drawing and winding to obtain antioxidant thermal conductive PPS fibers.
9. The method for preparing the oxidation-resistant thermally conductive PPS fiber according to claim 8, characterized in that: The extrusion granulation adopts a twin-screw extruder, the extrusion temperature is 260° C. to 330° C., and the screw speed is 200 to 400 rpm.
10. The method for preparing the oxidation-resistant thermally conductive PPS fiber according to claim 8, characterized in that: The extruder temperature of the extrusion melt is 270°C to 320°C; And / or, the spinneret temperature of the spinneret is 300°C to 330°C.
11. The method for preparing the oxidation-resistant thermally conductive PPS fiber according to claim 8, characterized in that: The temperature of the hot stretching is 90° C. to 150° C., the stretching multiple is 2 to 5 times, and the stretching speed is 1000 to 2000 m / min.
12. An antioxidant thermally conductive PPS fiber, characterized in that: Prepared by the preparation method described in claim 8.
Citation Information
Patent Citations
A polyphenylene sulfide antioxidant fiber based on layered nanoparticles and its preparation method
CN108360085B
An antioxidant polyphenylene sulfide / modified nano silica composite fiber and its preparation method
CN110205703B
Preparation method of antioxidant PPS fibers
CN113818246A
Polytetrafluoroethylene modified polyphenyl thioether material for automobile plastic part
CN103965635A
Preparation method of zinc oxide / graphene composite material and resistance type gas sensor
CN106442642A